The jungle book - Kipling, Rudyard, 1865-1936. (New York : Tor, 1992)
Mowgli, left alone in the jungle as a toddler after his parents are run off by Shere Khan, a Bengal tiger, grows to adulthood with the help of kind animals, always knowing his own showdown with the tiger is yet to come.
"A Tom Doherty Associates book.".
Wilson's Children.
3-4
Young Adult
Keywords: Animals -- Juvenile fiction; Jungles -- Juvenile fiction; Mowgli (Fictitious character) -- Juvenile fiction; Animals -- Fiction; Jungles -- Fiction; Mowgli (Fictitious character) -- Fiction; Animals -- Fiction; Jungles -- Fiction; Mowgli (Fictional character) -- Fiction; Short stories; India -- Juvenile fiction; India -- Fiction; India -- Fiction